INFLUENCE OF AGELESS LIQUID WITH OR WITHOUT PIPERINE ON SODIUM IODATE-INDUCED RETINAL DEGENERATION IN SPRAGUE-DAWLEY RATS - SHAKTA MANI SATYAM; LAXMINARAYANA BAIRY KURADY (International Journal of Pharma and Bio Sciences, 2016)
To study the effect of ageless liquid on sodium iodate-induced retinal degeneration in Sprague-Dawley rats. Retinal degeneration was induced by single intraperitoneal injection sodium iodate to adult Sprague- Dawley rats weighing 100–250 g. Ageless liquid in three different doses were given for 45 days. On day 46, the rats were sacrificed and eyes were removed and processed for estimation of malondialdehyde (MDA), reduced glutathione (GSH), ATP and TGF-β content, activity of catalase (CAT) and superoxide dismutase (SOD). The sodium iodate treated rats showed a significant increase in MDA, and a significant decrease in GSH, SOD, catalase, TGF-1β and ATP level compared to control rats suggesting the retinal damage. Three different doses of ageless liquid with piperine and without piperine significantly reversed the retinal damage done by sodium iodate. The retinoprotective potential was found to be better for ageless liquid with piperine in comparison with ageless liquid without piperine and maximum therapeutic benefit was observed at 16 mg/kg of ageless liquid with piperine.